2015
DOI: 10.1089/jir.2014.0135
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of CXCL5 in HIV-1-Infected Macrophages and Its Functional Consequences on CNS Pathology

Abstract: Human immunodeficiency virus-1 (HIV-1)-infected monocytes/macrophages and microglia release increased levels of proinflammatory cytokines and chemokines, including ELR + (containing glutamic acid-leucine-arginine motif) chemokines. To investigate the role of HIV-1 infection on chemokine regulation, monocyte-derived macrophages (MDMs) from normal donors were infected with HIV-1 and the expression of chemokines and their downstream biological functions were evaluated. Among the tested chemokines, CXCL5 was upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…It remains to be defined whether differences in target organs, the nature and severity of the inflammatory insult, the cells producing CXCL5, or local processing of CXCL5 contribute to dissimilarities in neutrophil recruitment in these models. To this end, previous studies have suggested that CXCL5 can be produced by hematopoietic as well as stromal cells, and we have shown that expression of this neutrophil chemokine is regulated by signaling through MyD88 in cardiac macrophages (36, 37). …”
Section: Discussionmentioning
confidence: 84%
“…It remains to be defined whether differences in target organs, the nature and severity of the inflammatory insult, the cells producing CXCL5, or local processing of CXCL5 contribute to dissimilarities in neutrophil recruitment in these models. To this end, previous studies have suggested that CXCL5 can be produced by hematopoietic as well as stromal cells, and we have shown that expression of this neutrophil chemokine is regulated by signaling through MyD88 in cardiac macrophages (36, 37). …”
Section: Discussionmentioning
confidence: 84%
“…In addition, inhibitors of neutrophil elastase, which are involved in neutrophil migration and neutrophil-mediated tissue damage, have been tested in experimental trials such as Sivelestat [ 7 , 33 35 ]. Other studies also indicated that the increased ENA 78 amplified the pro-inflammatory cytokine response, which had a direct chemo-attracting effect on neutrophils [ 36 39 ]. Therefore, we studied ENA 78 and found that it was dramatically increased in the NMO patients (vs. HC, P < 0.001; vs. MS, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Following their infection with HIV, M/M are known to mediate the transmigration of HIV infection across the blood–brain barrier (Williams et al., ). Several studies have identified specific changes facilitating the spread of HIV infection to brain by M/M (Buckner et al., ; Guha et al., ). A direct evidence supporting the involvement of these cells in HIV propagation and maintenance has been demonstrated previously (Collins et al., ; Harman et al., ; Kramski et al., ).…”
mentioning
confidence: 99%